2016
DOI: 10.20849/abr.v1i1.29
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Financial Compensation and Organizational Commitment among Malaysian Bank Workers

Abstract: <p>This research examines the relationship between financial compensation and organizational commitment among workers in the banking industry, Malaysia. This research is significant in addressing the preceding gap on the types of financial compensation such as salaries, bonuses and merit pay with a stronger relationship with organizational commitment. Although these variables have been widely studied, few studies have explored their relationship to organizational commitment. Quantitative methodology is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 14 publications
1
29
0
8
Order By: Relevance
“…In Rizal, Idrus, Djumahir and Mintarti (2014), compensation was defined as a mechanism for encouraging and motivating employees for the purpose of achieving organisational goals and objectives. According to Kee, Ahmad and Abdullah (2016), compensation is one of the strategies of human resource management for achieving organisational goals, towards sustaining the growth of the organisation. Munap, Mohd and Abdul (2013) had earlier identified compensation as a tool for attracting, motivating, retaining and gaining commitment of high-performers in the workplace.…”
Section: Compensation Systemmentioning
confidence: 99%
“…In Rizal, Idrus, Djumahir and Mintarti (2014), compensation was defined as a mechanism for encouraging and motivating employees for the purpose of achieving organisational goals and objectives. According to Kee, Ahmad and Abdullah (2016), compensation is one of the strategies of human resource management for achieving organisational goals, towards sustaining the growth of the organisation. Munap, Mohd and Abdul (2013) had earlier identified compensation as a tool for attracting, motivating, retaining and gaining commitment of high-performers in the workplace.…”
Section: Compensation Systemmentioning
confidence: 99%
“…However, several studies conducted in the West show contradictory evidence reporting that compensation has no significant impact on OC (Bhagat & Chassie, 1981;Malhorta, Budhwar, & Prowse, 2007;Shore & Barksdale, 1998). In Malaysian settings, some studies found that financial compensation and OC were positively correlated (Ibrahim & Boerhaneoddin, 2010;Kee, Ahmad, & Abdullah, 2016;Normala, 2010;Queiri & Dwaikat, 2016). This leads us to the following hypothesis:…”
Section: Satisfaction With Personnel Evaluationmentioning
confidence: 91%
“…Other studies such as by Alamelu et al, (2015), in the manufacturing industry in India, shows that employee compensation for commitment has a significant and positive influence. Then, Kee et al, (2016), in the banking industry in Malaysia showed a significant influence between the relationship of compensation and commitment. In the food industry in Kenya carried out by Milgo et al, (2014), showed a significant influence between compensation and commitment.…”
Section: The Effect Of Empowerment On Organizational Commitmentsmentioning
confidence: 99%